Legal Protection against Women Which Do Criminal Actions of Abortion from Victims of Rape for Justice - Farida Farida; Sri Kusriyah (Jurnal Daulat Hukum, 2020)
This study aims to identify and describe the legal protection of women perpetrators of the crime of abortion, victims of rape based on positive law in Indonesia in order to realize justice. This study uses a normative juridical approach, which is descriptive analysis. The data used is secondary data obtained through library research, which is then analyzed qualitatively. The results of this study are legal protection for women perpetrators of abortion, victims of rape based on positive law in Indonesia to achieve justice that in Article 48 of the Criminal Code that the perpetrator's actions are committed due to coercion, then they will not be convicted. The perpetrator was released from punishment on the grounds of forgiveness, whereas in the Republic of Indonesia Act No. 36 of 2009, that abortion is allowed due to indications of a medical emergency that threatens the life of the mother and pregnancy due to rape, given the trauma caused by rape that must be experienced by women who are victims of rape is very severe.